Harsh parenting and preschool children’s screen time: the mediating role of parent–child relationships and the moderating effect of mindful parenting - Zhang, Caili (Frontiers in Psychology, 2025)
IntroductionExcessive screen time among preschoolers is a growing public health concern. This study examined associations between harsh parenting and children’s screen time, testing parent–child relationship quality as a mediator and mindful parenting as a moderator.MethodsA cross-sectional survey was administered to 482 parents from four kindergartens in China (Mage = 36.0 years, SD = 3.89). Parents completed validated scales assessing harsh parenting, parent–child relationship quality, mindful parenting, and children’s daily screen time. A moderated mediation model was tested.ResultsHarsh parenting showed an indirect association with greater child screen time through poorer parent–child relationships. Mindful parenting moderated the link between harsh parenting and parent–child relationship quality, such that higher mindful parenting buffered the negative impact of harsh parenting, attenuating the indirect effect on screen time.DiscussionFindings indicate that strengthening parent–child relationship quality and fostering mindful parenting may mitigate the influence of harsh parenting on preschoolers’ screen use. Interventions promoting positive, mindful parenting practices could help reduce excessive screen time in young children.